Recente vondsten betreffende vroege grafsculptuur in Nederland, dertiende en veertiende eeuw (Bulletin KNOB, 1993)
Over the last twenty-five years several pieces of early funerary sculpture have come to light in the Netherlands. Some of them have not yet been published, others have been mentioned but not always in easily accessible periodicals. Here a survey of them is given, concentrating on the finds that have not yet been described and on some new insights procured by the others.In the medieval church of Lochem a piece of sandstone of a sacrament house was found in about 1973, the backside of which showed an Orans-figure and the words requie(m) and anim(am). The original funerary use of this memorial stone is clear, while stylistically it may probably date from the 9th or the 10th century. As such it deserves more notice then it has received up to now.Three new finds can be added to the group of sarcophagus lids with the representation of the deceased in low relief as found along the northern coastal region. At Vollenhove a lid was found in 1991 during extension works on the marina there. It shows the figure of a man with his hands on his stomach within a border consisting of ropes, while at the top a separate compartment shows a tiny figure standing for the elevatio animae scene.The lower right hand part of a similar slab at Rolde, already known but wrongly interpreted, is shown to belong to the same group. The extraordinary slab at Holwierde showing a husband and wife holding each other has not yet been dealt with in Dutch art-historical literature, though it is mentioned in the English handbook by Greenhill on incised effigial slabs.All three slabs are made of Bentheimer sandstone and can be dated back to the end of the 12th or the beginning of the 13th century. The whole group of these effigial slabs, and some fourteen are now known in the Netherlands and in northern Germany, can be described as provincial products derivative from funerary works of art in Westphalia in the 12th century (at Iburg and Riesenbeck).As to great tombs with effigies, the double tomb to Count Gerhard and his wife at Roermond is shown to be original and still on its original site in the middle of the former abbey church, in spite of doubts expressed in the handbook on tomb sculpture by Bauch. Attention is further drawn to the great tombs with giants that are made of Namur stone (at Gorinchem, Utrecht and Ysselstein), especially as they are still often stated to be of the better-known Tournai stone.Of the early-incised effigial slabs found in the present-day Netherlands, those at Velsen, Nijmegen and two at Maastricht are dealt with here. The one at Velsen deserved greater attention because of the special technique of taille d'épargne that is employed. The slab at Nijmegen to Coene Boem and his wife Karstine (early 14th-century) is mentioned because the name of Coene Boem has been found to refer to a wine merchant who paid a Rhine toll at Lobith in 1306 and 1307.The most recent find, in Maastricht on the site of the Friars' church in 1990, shows the lower part of an incised knightly figure standing on a dragon. The name of the knight has not been preserved but the date has, 1273, and as such it is one of the very few early-incised slabs commemorating knights in the Netherlands.